Change Detection in Hour-Ibn Nnjam / Middle of IRAQ by Using WaterIndex (W.I) Algebra - AL-Saedi, Zeyad; AL-Muthan, Ahmad (Iraqi Journal of Science, 2024)
Change detection is one of the most widely used processing techniques in remotesensing. It is a process of identifying differences in the state of a geographic featureor phenomenon by monitoring at different times. In order to detect the changes in aphenomenon, the function Water Index (WI) is used to identify changes in watercontent of the marsh during different periods of time. Landsat satellite data is usedof sensors MSS for the years 1974 &1992 and sensors TM 1984 and ETM sensorsfor the years 2003, 2006, 2009 By using Arc GIS software, the results are convertedto thematic maps which represent water index coefficient through multiple years, aswell as the use of Erase tool in the toolbox in the Arc GIS software, in order to findout the increase and decrease of the water content of the Marsh during the pastyears. The results showed that there is an increase in the area of the marsh in 1974and 1984 and 1992 with an areas 210, 237, 219 km2 , respectively and a decrease in2003, 2006 and 2009 of 52, 58, 74 km2, respectively.